DOMINASI HABITUS DALAM PRAKTIK KHITAN PEREMPUAN DI DESA KUNTU DARUSSALAM KABUPATEN KAMPAR RIAU (Aplikasi Praktik Sosial Pierre Boudieu dalam Living Hadis) - Hikmalisa Hikmalisa (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
Understanding common sense surrounding society where people act according to their interpretation toward hadith of the prophet as well Qur’anic verses and command is an essential meaning of living hadith. This paper begins with new alternative of perspective for living hadith, since there are obvious possible interpretations toward a hadith within a complex society that lead to various acts. In addition to that, the different act will be analyzed by Bourdieu’s theory of practice in order to see that the dynamic of practice in such society entail that complexity of interpretations. Female mutilation practice in Kuntu Darussalam village is the object of study in this paper, where majority of people has had perceived the practice asas an unquestioned Doxa for every individual, preached by Ulama repetitively. The latest agent plays assertively for his symbolic modal of the cultural village, unlike the secondary role (e.i. medical agent)who apprehensively stands for different habitus within the society.